Fenomena Media Periklanan terhadap Citra Kota Denpasar, Studi Kasus di Beberapa Persimpangan Jalan Utama Kota Denpasar - Kusuma Putra, I Gusti Ngurah Bagus; Suartika, Gusti Ayu Made (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 5 No 2 (2018): October 2018DO - 10.24843/JRS.2018.v05.i02.p03, 2018)
This study examines interferences brought by the placement of advertising elements on a public sphere. Since areas surrounding major road intersections are the most favored venues for advertisers and their advertisements, the study selects such areas exist across Denpasar City (Bali) as case studies. This research is designed to meet three goals. First is to pinpoint as to how intersections have been utilized as venues for advertising purposes. Second is to analyze various predicaments following the employment of a public spheres as a settings for advertisements. This analysis focuses on functional and regulatory concerns. Third is to develop alternative methods for future accommodation of advertisements, thus they will caused the least interruptions to the quality of spaces, the wider functions and roles of the public spheres, as well as having the slightest likelihood to ruin the image of a city as a whole. The study implements qualitative research approaches, supported by 22 sets of thorough photographic documentation recording advertisements surveyed at five different road intersections. The study construes that the consented acts to use intersections for advertising related purposes does not go in line with the formation of culturally friendly city, the image that Denpasar intends to be associated with. This message becomes the main consideration in instigating alternative methods for future accommodation of advertisements in an urban area, such as Denpasar. Keywords: advertisement, intersection, culture, public space